PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Novira, Rajista; Miaz, Yalvema; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to know the effect of using the Problem Based Learning (PBL) model on Student Critical Thinking Ability at Thematic Learning at 5th grade of Elementary School in Group II Long Guguk of Bukittinggi City in the 2018/2019 school year. This research is a quasi experimental design with nonequivalent control group design. The population of this research is the students of 5th grade of elementary school in Group II Guguk Panjang of Bukittinggi City. The sample of this research is the 5th grade students of  SDN 02 Percontohan of Bukittinggi City consisting of two classes namely VB and VC class with the number of students each 34 students. Sampling was done by simple random sampling. Based on the research that has been done, obtained tcount > ttable that is 2,06 > 1,99 with α = 0,05 so it can be concluded Ha accepted that there is influence the use of Problem Based Learning (PBL) model on Student Critical Thinking Ability at Thematic Learning at 5th grade of Elementary School in Group II Guguk Panjang of Bukittinggi City.Keyword : Problem Based Learning (PBL) model, Critical Thinking Ability, Thematic Learning